2000
DOI: 10.1017/s0007123400210296
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘Clarity of Responsibility’ Important for Economic Voting? Revisiting Powell and Whitten's Hypothesis

Abstract: In the words of Martin Paldam, comparative economic voting studies suffer from a 'great instability'-i.e., economic effects appear in some countries at some times, but not others, and tend to be weak and inconsistent across studies. 1 Powell and Whitten propose a possible solution to the 'instability' of cross-national voting studies: 'to explain differences in retrospective economic voting across nations and over time we must take account of the political context within which elections take place'. 2 More spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 4 publications
1
37
1
4
Order By: Relevance
“…This problem is not exclusive to decentralised systems but is associated with other forms of division of powers, such as coalition governments. Research has extensively dealt with the impact of other forms of divided government on electoral accountability (Powell & Whitten 1993;Leyden & Borrelli 1995;Royed et al 2000;Lowry et al 1998;Anderson 2006b;Anderson 2000;Duch & Stevenson 2008: 252ff). 5.…”
Section: Discussionmentioning
confidence: 99%
“…This problem is not exclusive to decentralised systems but is associated with other forms of division of powers, such as coalition governments. Research has extensively dealt with the impact of other forms of divided government on electoral accountability (Powell & Whitten 1993;Leyden & Borrelli 1995;Royed et al 2000;Lowry et al 1998;Anderson 2006b;Anderson 2000;Duch & Stevenson 2008: 252ff). 5.…”
Section: Discussionmentioning
confidence: 99%
“…In the classic model of electoral accountability, voters use elections to reward or punish politicians on the basis of their past performance (Fiorina 1981). However, elections can only work as an effective retrospective mechanism to control governments insofar as there is clarity of responsibility (Key 1966;Ferejohn 1986;Royed et al 2000;Powell 2000). If citizens cannot clearly distinguish spheres of authority across levels of government, voters' electoral punishments or rewards may be barely connected to incumbents' past performance, which takes the whole classic reward-punishment model of electoral accountability to task.…”
Section: Attributions Of Responsibility Clarity Of Responsibility Anmentioning
confidence: 99%
“…There is a large body of literature that shows that complex institutional contexts complicate responsibility attribution and, in turn, make it difficult for voters to hold governments to account. Different forms of horizontal division of powers, such as coalition governments or bicameral opposition, are associated with low levels of clarity, which attenuates the economy-voting relationship (Anderson 2000;Hobolt & Tilley 2014a;Lowry et al 1998;Nadeau et al 2002;Powell & Whitten 1993;Royed et al 2000). More recent contributions have shown that the institutional conditions that weaken the rewardpunishment model for economic outcomes may also attenuate voting on issues other than the economy, such as healthcare (Hobolt et al 2013) or European integration (De Vries et al 2011).…”
Section: Attributions Of Responsibility Clarity Of Responsibility Anmentioning
confidence: 99%
“…The few papers to analyse the effects of taxation on multiparty systems have followed this procedure (see for example Royed et al, 2000, Landon and Ryan, 1992, and Vermeier and Heyndels, 2004. However, we also use the vote share of the main party in the government in addition to this variable, which is the 6 The most relevant in terms of local governments controlled are CiU and ERC (right and left-wing, respectively, both in Catalonia), UV (right-wing, in Valencia), and BNG (left-wing, in Galicia), but there are one or two in each region.…”
Section: The Vote Equationmentioning
confidence: 99%